Optimization of hardness test results in welding dissimilar metal S304 H and Incoloy 800H - Hendra Dwipayana; A. Novianda (TURBO [Tulisan Riset Berbasis Online], 2023)
The paper is written fully in Bahasa Indonesia (except the abstract is written in Bahasa Indonesia and English) using Times New Roman font type, 12 font size and single row space. The paper size is A4 (21 × 29.7 cm) and the author is recommended not to write more than 10 pages. The main article content covers abstract, introduction, literature review, method, result, and conclusion. Pictures, tables and equations can be included in the article. Top, bottom, and right / left margin of the paper are 2.54 cm, respectively. The number of words in the abstract is around 200 words. The abstract should mention briefly the background, objectives, method, and main conclusions. Following the abstract, write down five keywords for indexing. An unusual abbreviation should be defined clearly after the first mention.